2011
DOI: 10.3892/ijo.2011.1155
|View full text |Cite
|
Sign up to set email alerts
|

Interferon/STAT1 and neuregulin signaling pathways are exploratory biomarkers of cetuximab (Erbitux�) efficacy in KRAS wild-type squamous carcinomas: A pathway-based analysis of whole human-genome microarray data from cetuximab-adapted tumor cell-line models

Abstract: Abstract. KRAS mutation status is being used as the sole biomarker to predict therapeutic efficacy of cetuximab in metastatic colorectal cancer (mCRC). A significant number of mCRC patients with KRAS wild-type (WT) tumors, however, do not benefit from cetuximab. We are also lacking efficacy predictors in head and neck squamous cell carcinomas with an intact KRAS signaling and in non-small cell lung cancer in which KRAS mutations do not predict cetuximab efficacy. We recently established pre-clinical models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…EGFR-dependent down-regulation of IRF1 and, as a consequence, of IRF1-dependent type III IFN-λ, was shown to be the strategy exploited by some respiratory viruses to suppress the antiviral response in human airway epithelial cells, a mechanism effectively reverted by EGFR inhibition [42]. Finally, very similar to what we found in keratinocytes, cetuximab induced type I IFN/STAT1 signature in A431 human epidermal carcinoma cell line harbouring oncogenic Ras, with enhanced transcription of STAT1, a number of antiviral effectors (IFIT1, IFITM1, RSAD2, OAS1, and OAS2 among others), and also pro-inflammatory mediators, including TNF-α and very high lymphotoxin beta [43]. From these and our own findings, we can reasonably hypothesize that sustained activity of the EGFR/Ras/Raf/MEK/ERK phosphorylation cascade might exert a permanent, tonic regulation on IRF1 functional state, leading to effective control on the transactivation of a subset of genes which includes IFN-κ.…”
Section: Discussionsupporting
confidence: 68%
“…EGFR-dependent down-regulation of IRF1 and, as a consequence, of IRF1-dependent type III IFN-λ, was shown to be the strategy exploited by some respiratory viruses to suppress the antiviral response in human airway epithelial cells, a mechanism effectively reverted by EGFR inhibition [42]. Finally, very similar to what we found in keratinocytes, cetuximab induced type I IFN/STAT1 signature in A431 human epidermal carcinoma cell line harbouring oncogenic Ras, with enhanced transcription of STAT1, a number of antiviral effectors (IFIT1, IFITM1, RSAD2, OAS1, and OAS2 among others), and also pro-inflammatory mediators, including TNF-α and very high lymphotoxin beta [43]. From these and our own findings, we can reasonably hypothesize that sustained activity of the EGFR/Ras/Raf/MEK/ERK phosphorylation cascade might exert a permanent, tonic regulation on IRF1 functional state, leading to effective control on the transactivation of a subset of genes which includes IFN-κ.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, we observed STAT-1, HLA class I upregulation in cetuximab-treated patients in a novel neoadjuvant trial, suggesting that EGFR inhibition and/or IFNγ release contributes to the reversal of HLA downregulation. Results from recent studies also indicated an immunosuppressive effect of EGFR signaling on STAT1-dependent HLA class I and CIITA genes (38,39). However, HLA class I and CIITA are modulated by both total STAT1 and p-STAT1 (40,41), and a recent report also indicates that EGFR inhibitors reduces PD-L1 expression in lung tumors (42), suggesting multiple immune escape mechanisms mediated by EGFR signaling.…”
Section: Discussionmentioning
confidence: 94%
“…Western blots were performed using an SDS–PAGE electrophoresis system as described previously (Oliveras-Ferraros et al , 2011a, 2011b), employing anti-AREG (Santa Cruz Biotechnology, Santa Cruz, CA, USA, cat. no.…”
Section: Methodsmentioning
confidence: 99%
“…Our recently described transcriptome signature for Ctx efficacy in cultured models of squamous cell carcinomas (SCCs) revealed that the molecular function of Ctx depended on high expression levels of genes encoding EGFR ligands (such as AREG and EREG ) concomitant with downregulation of DUSP -regulated EGFR inhibition (Oliveras-Ferraros et al , 2011a, 2011b). A dramatic downregulation of AREG/EREG mRNA expression, but not of other EGFR ligands, has been found to correlate with loss of Ctx efficacy (Oliveras-Ferraros et al , 2011a, 2011b).…”
mentioning
confidence: 99%
See 1 more Smart Citation